the answer is 3x2
3x2 + 27x +60
24x6 + 12x4 + 15x2 factor the greatest common factor, 3x2 = 3x2(8x4 + 4x2 + 5)
3x2+7-6 = (3x-2)(x+3) when factored
3x2 + 48 + 192 = 3x2 + 240 = 3 (x2+ 80)
While it is possible to factor 3x2 from both of these and get 3x2(4 - 1), it's a lot easier to subtract 3x2 from 12x2 and get 9x2
factor out a 3x 3x(x-3)=3x2-9x
the answer is 3x2
-8x + 3x2 - 3
3x2 + 27x +60
To factor the expression 3x^2 - 9x^3, we first need to find the greatest common factor (GCF) of the two terms. The GCF of 3x^2 and 9x^3 is 3x^2. We can factor out 3x^2 from both terms to get 3x^2(1 - 3x). Therefore, the factored form of 3x^2 - 9x^3 is 3x^2(1 - 3x).
24x6 + 12x4 + 15x2 factor the greatest common factor, 3x2 = 3x2(8x4 + 4x2 + 5)
yes
3X2 + 6X + 9 3(X2 + 2 + 3) -----------------------3 is a common factor of all terms
x(3x-2)
2(3x2 - 2)
x(3x-4)